Manajemen Kearsipan Dalam Meningkatkan Pelayanan Administrasi pada MAN 1 Kepahiang - Susanti, Fitri; Murniyanto, Murniyanto; Deriwanto, Deriwanto (El-Idare, 2023)
This research aims to describe how the implementation of archive management improves the quality of administrative services at MAN 1 Kepahiang. This qualitative study involves key informants such as the head of administration, head of the madrasah, deputy head of the madrasah, teachers, and students. Data collection techniques include observation, interviews, and documentation. The results reveal that archive management at MAN 1 Kepahiang encompasses procedures for archive creation, storage, maintenance, transfer, and depreciation. Challenges include a lack of human resources for archive management, insufficient storage facilities, and a lack of training in archive management. However, the presence of adequate storage warehouses and efficient administrative staff supports archive management. Looking ahead, it is hoped that the school will facilitate training for archivists and allocate a dedicated space for inactive archive storage to optimize and enhance administrative services at MAN 1 Kepahiang.